Production and operations management - Chary, S.N (McGraw Hill Education (I) Pvt. Ltd, 2014)
Production and operations management / Chary, S.N. -- New Delhi: McGraw Hill Education (I) Pvt. Ltd., 2014 658.5 C469e5 5th ed No. of Copies : 1